Avaliação histomorfométrica de implantes dentários confeccionados em titânio comercialmente puro Grau IV e liga de Ti-6AI-4V Grau V - Silva, Jonathan Ribeiro da (2014)
Objective: The aim of this study is perform a histomorphometric analysis between two different implants substrates available, grade IV (commercially pure titanium) and grade V (alloy Ti-6Al-4V). Materials and Methods: 18 implants of each alloy were installed in 18 male beagle dogs. The implant length was 10 mm and 4.6 mm in diameter (Signo Vinces, modelo Duo, Campo Largo, Paraná, Brazil). After euthanasia at 1, 3, and 6 weeks, the implants were subjected to histomorphometric analysis. Results: There was a progressive increase in BIC analyzed when the 1st, 3rd, and 6th week independent of the substrate. The BAFO showed an increase from the 1st to the 3rd week, however when compared the 3rd and 6th week, bone formation remained unchanged. There was no difference between the histomorphometric analysis from grade IV and grade V. Conclusion: The experimental and control groups presented no differences biocompatible for histomorphometric analysis, future studies are needed to define the clinical indications for implant dentistry rated substrate.